Den Dualismus überlisten: Negative Dialektik, Cat’s Cradle und die Idee unverstellter Erkenntnis - Weber, Jutta (Dualitäten)

An Approach for Self-Reconfiguring and Fault-Tolerant Distributed Real-Time Systems - Klobedanz, Kay; Müller, Wolfgang; Rettberg, Achim
In this paper we present an approach for the self reconfiguration of distributed micro-controllers for increased fault tolerance. Based on a modified distributed system topology utilizing a time division multiple access (TDMA) protocol, i.e., Flex Ray, we present a self-organized distributed coordinator concept which performs the self-reconfiguration in the case of node failures. We introduce a distributed coordinator, which utilizes redundant slots in the Flex Ray communication schedule and combines messages in configured protocol frames and slots to avoid a complete bus restart. As such, the self-reconfiguration is realized by means of predetermined information about resulting changes in the communication dependencies and (re-)assignments determined in the design phase. To retrieve the necessary information, we present an analytical approach, which determines a combined solution for the initial configuration and all possible reconfigurations for the remaining nodes of the Flex Ray network in case of node failures. Hence, through this method we can design self-reconfiguring network-based systems enabling the handling of node failures for an increased fault tolerance.
Keywords: Real time systems; Fault tolerant systems; Schedules; Protocols; Redundancy; Delay

Towards an Enhanced UVM for SystemC - Oliveira, M. F.; Kuznik, Christoph; Müller, Wolfgang; Esen, V.; Ecker, W. (Proceedings of the Design & Verification Conference (DVCon))

Mutation-Analysis Driven Functional Verification of a Soft Microprocessor - Xie, Tao; Müller, Wolfgang; Letombe, Florian (Proceedings of SOCC2012)
This paper proposes a quality driven, simulation based approach to functional design verification, which applies mainly to IP-level HDL designs with well specified test instruction format and is evaluated on a soft microprocessor core MB-LITE [5]. The approach utilizes mutation analysis as the quality metric to steer an automated simulation data generation process. It leads to a simulation flow with two phases towards an enhanced mutation analysis result. First in a random simulation phase, an in-loop heuristics is deployed and adjusts dynamically the test probability distribution so as to improve the coverage efficiency. Next, for each remaining hard-to-kill mutant, a search heuristics on test input space is developed to iteratively locate a target test, using a specific objective cost function for the goal of killing HDL mutant. The effectiveness of this integrated two-phase simulation flow is demonstrated by the results with the MB-LITE microprocessor IP.
Keywords: Analytical models; Hardware design languages; Microprocessors; Cost function; Data models; Search problems; IP networks

An IP-XACT-TO-SystemC Model Generator for Mutation Analysis - Xie, Tao; Müller, Wolfgang (Proceedings of the MeCoES’12)

Schauspielmusik - Tumat, Antje (Wagner-Handbuch)

Uneingeleitete Nebensätze mit konditionaler Semantik im Mittelniederdeutschen - Wallmeier, Nadine (Niederdeutsche Syntax)

Teaching Experience - improving teacher education with experiential learning - Behr, Teresa; Temmen, Katrin (International Journal on New Trends in Education & their Implications (IJONTE))

When ideas circulate. A walk across disciplines and different uses of the ‘capability approach’ - Dahmen, Stephan; Bussi, Margherita (Transfer: European Review of Labour and Research)

Gender & Art: Selbstbilder und Selbstkonzepte in den Künsten (GENDER. Zeitschrift für Geschlecht, Kultur und Gesellschaft)
Die Vorstellung der künstlerischen Schöpfungskraft als ‚männliche Gabe‘ tradiert sich seit Jahrhunderten und nimmt Einfluss auf das Schaffen von Künstlerinnen und Künstlern. Die feministische Kunst offenbart diese Normierung und bietet dadurch Ansätze zur Auseinandersetzung mit dem (Selbst-)Verständnis von Kunst und Kunstschaffenden vor dem Hintergrund des anhaltenden Diskurses über Geschlecht. Die Beiträge in diesem Heft zeigen Beispiele einer solchen Herangehensweisen aus unterschiedlichen künstlerischen Genres.